Group Belongingness and Procedural Justice Social Inclusion and Exclusion by Peers Affects the Psychology of Voice. [article] . - van Prooijen, Jan-Willem
The authors focus on the relation between group membership and procedural justice. They argue that whether people are socially included or excluded by their peers influences their reactions to unrelated experiences of procedural justice. Findings from 2 experiments corroborate the prediction that reactions to voice as opposed to no-voice proecedures are affected more strongly when people are included in a group than when they are excluded from a group. These findings are extended with a 3rd experiment that shows that people who generally experience higher levels of inclusion in their lives respond more strongly to voice as opposed to no-voice procedures. It is concluded that people's reactions to procedural justice are moderated by people's level of inclusion in social groups. -- (from the author)
Keywords: Psychology-Periodicals.